Macrolide/Azalide therapy for nodular/bronchiectatic mycobacterium avium complex lung disease - Wallace, Jr, Richard J; Brown-Elliott, Barbara A; McNulty, Steven; Philley, Julie V; Killingley, Jessica; Wilson, Rebecca W; York, Deanna S; Shepherd, Sara; Griffith, David E (Chest, 2014)
There is no large study validating the appropriateness of current treatment guidelines for Mycobacterium avium complex (MAC) lung disease. This is a retrospective single-center review evaluating the efficacy of macrolide/azalide-containing regimens for nodular/bronchiectatic (NB) MAC lung disease. Patients were treated according to contemporary guidelines with evaluation of microbiologic responses. Macrolide susceptibility of MAC isolates was done at initiation of therapy, 6 to 12 months during therapy, and on the first microbiologic recurrence isolate. Microbiologic recurrence isolates also underwent genotyping for comparison with the original isolates. One hundred eighty patients completed > 12 months of macrolide/azalide multidrug therapy. Sputum conversion to culture negative occurred in 154 of 180 patients (86%). There were no differences in response between clarithromycin or azithromycin regimens. Treatment regimen modification occurred more frequently with daily (24 of 30 [80%]) vs intermittent (2 of 180 [1%]) therapy (P = .0001). No patient developed macrolide resistance during treatment. Microbiologic recurrences during therapy occurred in 14% of patients: 73% with reinfection MAC isolates, 27% with true relapse isolates (P = .03). Overall, treatment success (ie, sputum conversion without true microbiologic relapse) was achieved in 84% of patients. Microbiologic recurrences occurred in 74 of 155 patients (48%) after completion of therapy: 75% reinfection isolates, 25% true relapse isolates. Current guidelines for macrolide/azalide-based therapies for NB MAC lung disease result in favorable microbiologic outcomes for most patients without promotion of macrolide resistance. Intermittent therapy is effective and significantly better tolerated than daily therapy. Microbiologic recurrences during or after therapy are common and most often due to reinfection MAC genotypes.